Pengaruh Profitabilitas, Leverage, dan Kepemilikan Manajerial Terhadap Nilai Perusahaan dengan Corporate Social Responsibility Sebagai Variabel Moderasi - Bima Andika Ivanda Putra; Sunarto Sunarto (Universitas Batanghari Jambi, 2021)
This study aims to analyze and test the effect of profitability, leverage, and managerial ownership on firm value with the moderating variable, namely Corporate Social Responsibility (CSR). The population used in this study is all manufacturing companies that have been listed on the Indonesia Stock Exchange (IDX) in the last three years, namely 2017-2019. The sampling method used in this study was purposive sampling technique. The results of this study explain that profitability and leverage do not have an effect on firm value, while managerial ownership has a negative effect on firm value. Corporate Social Responsibility (CSR) is able to moderate the effect of profitability and managerial ownership on firm value, while Corporate Social Responsibility (CSR) is unable to moderate the effect of leverage on firm value.